European white-collar crime: exploring the nature of European realities - Lord, Nicholas; Inzelt, Éva; Huisman, Wim; Faria, Rita (Bristol University Press, 2021)
Presenting an original series of provocative essays, this book offers a European framing of white-collar crime. Experts from different countries foreground what is unique, innovative, or different about white-collar and corporate crimes that are so strongly connected to Europe.